First autochthonous case of Opisthorchis felineus in Austria - Lisa-Maria Kulmer; Maria Sophia Unterköfler; Yasamin Vali; Ilse Schwendenwein; Nicole Luckschander-Zeller (Parasites & Vectors)
Abstract Background Opisthorchis felineus is a feline pathogen with zoonotic potential that can be a causative agent of human opisthorchiasis and cholangiocarcinoma. In Europe, O. felineus is particularly endemic in Eastern European countries, while this parasite has also been sporadically detected in Germany, Italy and northern Poland. Parts of Asia, such as Russia, Ukraine and Kazakhstan, are also affected. Methods A 7-year-old female neutered European Shorthair cat, without any traveling history, presented in May 2023 with weight loss, anorexia and vomiting. Results The cat showed increased liver enzyme activities, hyperbilirubinemia and hyperammonemia consistent with the suspected diagnosis of cholangitis with consecutive hepatoencephalopathy. Eggs of O. felineus were detected by routine cytological examination of bile smears and PCR confirmed O. felineus. Conclusions This is the first report of autochthonous O. felineus infection in Austria. Graphical Abstract